2021
DOI: 10.3389/fnut.2021.614105
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiotic Supplementation of PS128TM Improves Stress, Anxiety, and Insomnia in Highly Stressed Information Technology Specialists: A Pilot Study

Abstract: Background: Information technology (IT) is an industry related to the production of computers, information processing, and telecommunications. Such industries heavily rely on the knowledge and solutions provided by IT specialists. Previous reports found that the subjective stress scores were higher in IT specialists who developed diabetes, hypertension, and depression. Specific probiotics, known as psychobiotics, may alleviate stress and mood symptoms. This study aimed to examine whether an 8-week intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 64 publications
3
20
0
Order By: Relevance
“…2, 3, 4, and 5), suggesting that L. plantarum PS128 can be used as a laxative food supplement. A recent clinical study has also shown that daily administration of L. plantarum PS128 for eight weeks significantly improved self-perceived stress and GI symptoms in highly stressed information technology specialists [17], which supported the results of this study. However, in mice with Lop-induced constipation, the laxative effect of L. plantarum PS128 was relatively faint (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…2, 3, 4, and 5), suggesting that L. plantarum PS128 can be used as a laxative food supplement. A recent clinical study has also shown that daily administration of L. plantarum PS128 for eight weeks significantly improved self-perceived stress and GI symptoms in highly stressed information technology specialists [17], which supported the results of this study. However, in mice with Lop-induced constipation, the laxative effect of L. plantarum PS128 was relatively faint (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, there has been a move to using microbial consortia (multiple strains of probiotics) in order to improve efficacy or induce additive and synergistic effects. In healthy populations, reductions in stress, anxiety and depression after probiotic supplementation are repeatedly demonstrated [ 4 ▪ , 5 , 6 , 7 ▪ ]. In patient populations, recently improved clinical symptoms of depression were observed in an open labeled pilot study in depressed patients using the combination of Lactobacillus helveticus R0052 and Bifidobacterium longum R0175 (CEREBIOME) [ 8 , 9 ] and a reduction in anxiety symptoms in a population with Generalized Anxiety Disorder was elicited through a multistrain probiotic containing B. longum , B. bifidum , B. lactis and L. acidophilus [ 10 ▪▪ ].…”
Section: Probioticsmentioning
confidence: 99%
“…The use these remedy are often associated with endocrine and metabolic side effects, which involve changes in the composition of the gut microbiota, may result in disorders such weight loss, weight gain, metabolic syndrome, diabetes, hyperparathyroidism, hypothyroidism, hypertension and sexual dysfunction [ 46 ]. Thus, the adoption of less aggressive “therapy” to the host body need to be considered, such as “Psychobiotic Therapy” [ 52 - 56 ]. The main advantages of using psychobiotic therapy in maintaining mental health during the pandemic such as COVID-19 is that, because they are microorganisms that belong to microbial genera naturally found in the intestinal tract ( Fig.…”
Section: Discussionmentioning
confidence: 99%